Bahan Organik Terlarut dan Parameter yang Mempengaruhinya di Bagian Hilir Tukad Mati, Badung, Bali - Sholihin, Muhammad; Perwira, Ima Yudha; Ernawati, Ni Made (Current Trends in Aquatic Science; Vol 4 No 1 (2021), 2021)
This research aimed to determine the amount of dissolved organic matter (BOT) and its influencing factors in the downstream part of the Tukad Mati, Badung, Bali. The research was conducted in the downstream of Tukad Mati from July to September 2019. The parameters measured were BOT, TSS, Turbidity, TDS, NO3, DO, pH, and Temperature. The results showed the level of increase in BOT in the morning with an average of 22.1 mg/l and afternoon 24.3 mg/l had a difference of 2.2 mg/l, with a percentage increase of 9.95% . TDS measurement results in the morning and evening have an average value of 419 mg/l and 423 mg/l with a difference of 4 mg/l with a percentage decrease of 0.95%. The results of nitrate measurements in the morning and evening have an average value of 3.5 mg /l and 3.8 mg/l with a difference of 0.3 mg/l with a decrease percentage of 8.6%. The results of TSS measurements in the morning and evening had an average value of 8.9 mg/l and 11.8 mg/l with a difference of 11.8 mg/l with a reduction percentage of 32.5%.